Reality of secondary prevention pharmacological therapy of cardiovascular diseases in the city of Embu-Guaçu/SP - Dias, Fernanda Galvão Canda Kimura; Juliano, Yára; França, Carolina Nunes; de Souza, Patrícia Colombo (Journal of Health Care, 2021)
not only to decrease cardiovascular disease (CVD) morbidity and mortality, but also because it has an impact on quality of life. Objectives: The aim of this study was to evaluate secondary prevention drug therapy in patients with cardiovascular events who attend the Family Health Units of Embu-Guaçu. Patients and Methods: An observational, cross-sectional study was conducted with 68 patients who had experienced at least one cardiovascular event and who answered a questionnaire including socio-demographic data, cardiovascular event identification, prescribed medications, prescribers, and place of follow-up. Results: Among the cardiovascular events, stroke was the most prevalent (p
Keywords: cardiovascular agentes; cardiovascular dieeases; secondary prevention